Respuesta :

Answer:

[tex]( - \frac{1}{3} , - \frac{13}{3} )[/tex]

Step-by-step explanation:

The given system is

y = x - 4

y = -2x - 5

To solve this system, we equate both equations to get:

[tex]x - 4 = - 2x - 5[/tex]

[tex]x + 2x = - 5 + 4[/tex]

[tex]3x = - 1[/tex]

Divide both sides by 3 to get:

[tex]x = - \frac{1}{3} [/tex]

We substitute the value of x into the top equation to get:

[tex]y = - \frac{1}{3} - 4[/tex]

[tex]y = - \frac{1}{3} - \frac{12}{3} = - \frac{13}{3} [/tex]

ACCESS MORE